Positive electrode plate and non-aqueous electrolyte secondary battery

The positive electrode plate with specific lithium transition metal composite oxides balances high charging capacity and thermal stability by using a first active material with a high Li/M ratio and a second active material with a lower Li/M ratio and controlled particle sizes, enhancing the performance of non-aqueous electrolyte secondary batteries.

JP2024176844AActive Publication Date: 2024-12-19PRIME PLANET ENERGY & SOLUTIONS INC

Patent Information

Application Number
JP2023095674
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-09
Publication Date
2024-12-19
Estimated Expiration
2043-06-09

AI Technical Summary

Technical Problem

Non-aqueous electrolyte secondary batteries face a trade-off between high charging capacity and thermal stability, with increased charging capacity often leading to decreased thermal stability.

Method used

A positive electrode plate comprising a first lithium transition metal composite oxide with a specific lithium-to-transition metal molar ratio (Li/M) of 1.05 or more and a second lithium transition metal composite oxide with a smaller average particle diameter and a lower Li/M ratio of 1.04 or less, along with controlled particle sizes and nickel content, is used to balance charging capacity and thermal stability.

Benefits of technology

The solution enables a non-aqueous electrolyte secondary battery to achieve both high charging capacity and excellent thermal stability by optimizing the composition and properties of the electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024176844000005
    Figure 2024176844000005
  • Figure 2024176844000006
    Figure 2024176844000006
  • Figure 2024176844000001
    Figure 2024176844000001
Patent Text Reader

Abstract

To provide a positive electrode plate which can attain a high charge capacity and an excellent thermal stability at the same time.SOLUTION: The positive electrode plate includes: a first active material as a lithium transition metal composite oxide; and a second active material as a lithium transition metal composite oxide, the average particle diameter (D50) of the second active material being smaller than that of the first active material. The particle size of the second active material is 800 nm or larger. The ratio (Li / M) of the amount by mole of lithium (Li) in the first active material and the total amount by mole of the transition metal (M) is 1.05 or more, and the ratio (Li / M) of the amount by mole of lithium (Li) in the second active material and the total amount by mole of the transition metal (M) is 1.04 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode plate and a non-aqueous electrolyte secondary battery. [Background technology]

[0002] In non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries, it is known that a lithium transition metal composite oxide, which is a composite oxide of lithium and a transition metal, is used as the positive electrode active material contained in the active material layer of the positive electrode plate. Patent documents 1 to 3 disclose that the capacity, output, etc. can be improved by using a positive electrode plate using two or more types of lithium transition metal composite oxides with different particle sizes, etc. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2021-518049 [Patent Document 2] JP 2011-113825 A [Patent Document 3] International Publication No. 2021 / 065162 Summary of the Invention [Problem to be solved by the invention]

[0004] In non-aqueous electrolyte secondary batteries, increasing the charge capacity can result in a decrease in thermal stability, and therefore there is a demand for non-aqueous electrolyte secondary batteries that achieve both high charge capacity and excellent thermal stability.

[0005] An object of the present disclosure is to provide a positive electrode plate that can achieve both high charging capacity and excellent thermal stability, and a nonaqueous electrolyte secondary battery including the same. [Means for solving the problem]

[0006] [1] A first active material that is a lithium transition metal composite oxide, and a second active material that is a lithium transition metal composite oxide and has a smaller average particle diameter (D50) than the first active material, The crystallite size of the second active material is 800 nm or more; the ratio (Li / M) of the number of moles of lithium (Li) to the total number of moles of transition metals (M) in the first active material is 1.05 or more; A positive electrode plate, wherein the ratio (Li / M) of the number of moles of lithium (Li) to the total number of moles of transition metals (M) in the second active material is 1.04 or less.

[0007] [2] The positive electrode plate according to [1], wherein the ratio (Li / M) of the number of moles of lithium (Li) to the total number of moles of transition metals (M) in the first active material is 1.12 or less.

[0008] [3] The positive electrode plate according to [1] or [2], wherein the ratio (Li / M) of the number of moles of lithium (Li) to the total number of moles of transition metals (M) in the second active material is 0.98 or more.

[0009] [4] The positive electrode plate according to any one of [1] to [3], wherein a ratio (Li / M) of the number of moles of lithium (Li) to the total number of moles of transition metals (M) in the second active material is 1.01 or more.

[0010] [5] The positive electrode plate according to any one of [1] to [4], wherein a mass ratio of the first active material to the second active material (first active material / second active material) is 5 / 5 or more and 8 / 2 or less.

[0011] [6] The positive electrode plate according to any one of [1] to [5], wherein the first active material has an average particle diameter (D50) of 12 μm or more and 20 μm or less.

[0012] [7] The positive electrode plate according to any one of [1] to [6], wherein the second active material has an average particle diameter (D50) of 2 μm or more and 8 μm or less.

[0013] [8] The positive electrode plate according to any one of [1] to [7], wherein each of the first active material and the second active material contains 80 mol % or more of nickel (Ni) with respect to the total amount of transition metals.

[0014] [9] The positive electrode plate according to any one of [1] to [8], wherein the second active material is at least one of a single particle and a secondary particle formed by an aggregation of three or less primary particles.

[0015]

[10] An electrode assembly having a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate according to any one of [1] to [9]; and an electrolyte. Effect of the Invention

[0016] According to the positive electrode plate of the present disclosure, it is possible to provide a nonaqueous electrolyte secondary battery that can achieve both high charging capacity and excellent thermal stability. [Brief description of the drawings]

[0017] [Figure 1] 1 is a graph in which the charge capacity when a test cell (r1) having a positive electrode plate (r1) formed using a first active material is charged and the ratio of the capacity at a potential of 4.1 V vs. Li / Li+ or more are plotted against the ratio (Li / M) of the number of moles of lithium (Li) to the total number of moles of transition metals (M) in the first active material. [Diagram 2] 1 is a graph in which the charge capacity when a test cell (r2) having a positive electrode plate (r2) formed using a second active material is charged and the ratio of the capacity at a potential of 4.1 V vs. Li / Li+ or more are plotted against the ratio (Li / M) of the number of moles of lithium (Li) to the total number of moles of transition metals (M) in the second active material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] (Positive plate) The positive electrode plate of this embodiment can be used in a non-aqueous electrolyte secondary battery (hereinafter also referred to as a "secondary battery"). The positive electrode plate includes a first active material which is a lithium transition metal composite oxide, and a second active material which has a smaller average particle size (D50) than the first active material and is also a lithium transition metal composite oxide. The crystallite size of the second active material is 800 nm or more.

[0019] The lithium transition metal composite oxide is an oxide containing lithium and a transition metal. The transition metal contained in the lithium transition metal composite oxide may be at least one selected from the group consisting of nickel (Ni), manganese (Mn), cobalt (Co), aluminum (Al), and titanium (Ti), and is preferably at least one selected from the group consisting of Ni, Mn, Co, and Al, and more preferably at least one selected from the group consisting of Ni, Mn, and Co. The transition metal preferably contains Ni, Mn, and Co, and may contain Ni, Mn, Co, and Al.

[0020] The first active material and the second active material each independently contain Ni in an amount of preferably 80 mol % or more, more preferably 80 mol % to 98 mol %, or may contain 81 mol % to 95 mol %, or may contain 82 mol % to 90 mol % of Ni relative to the total amount of transition metals. By using the first active material and the second active material having Ni contents within the above ranges, it is possible to increase the capacity of the secondary battery.

[0021] The ratio (Li / M) of the number of moles of Li to the total number of moles of transition metals (M) in the first active material is 1.05 or more, may be 1.07 or more, or may be 1.09 or more. The ratio (Li / M) in the first active material is preferably 1.05 or more and 1.12 or less, may be 1.05 or more and 1.10 or less, may be 1.07 or more and 1.10 or less, or may be 1.07 or more and 1.09 or less.

[0022] The ratio (Li / M) of the moles of Li to the total moles of transition metals (M) in the second active material is 1.04 or less, may be 1.03 or less, or may be 1.02 or less. The ratio (Li / M) in the second active material is preferably 0.98 to 1.04, may be 1.00 to 1.04, more preferably 1.01 to 1.04, or may be 1.02 to 1.03. The compositions of the first active material and the second active material (lithium transition metal composite oxide) can be determined by high-frequency inductively coupled plasma (ICP) emission spectrometry.

[0023] As will be described in the manufacturing example of the embodiment described later, when the above ratio (Li / M) in the first active material is below 1.05, the total capacity when a test cell (r1) having a positive electrode plate (r1) formed using the first active material is charged is 4.1 V vs. Li / Li + The ratio of the capacity at potentials above 4.1V vs. Li / Li when the test cell (r1) was charged was 4.1V vs. Li / Li when the test cell (r1) was charged. + It is considered that if the capacity ratio at the above potential increases, the structural stability of the lithium transition metal composite oxide constituting the first active material decreases, and the lithium transition metal composite oxide is more likely to undergo a phase transition. As a result, it is presumed that the potential during charging of the secondary battery is more likely to increase, and the capacity ratio at that potential increases. The above capacity ratio is an index representing the thermal stability of the test cell (r1), and the smaller the capacity ratio, the more excellent the thermal stability. From this, it can be said that whether the above ratio (Li / M) of the first active material is 1.05 or more has a large effect on the thermal stability of the secondary battery.

[0024] In contrast, when the ratio (Li / M) in the second active material is 1.04 or less, the charge capacity per unit mass of the second active material can be increased when a test cell (r2) having a positive electrode plate (r2) formed using the second active material is charged (see the manufacturing example in the Examples described below, FIG. 2, and Table 2). On the other hand, when the ratio (Li / M) in the second active material exceeds 1.04, the charge capacity tends to decrease significantly (FIG. 2 and Table 2). From this, it can be said that whether the ratio (Li / M) of the second active material is 1.04 or less has a large effect on the magnitude of the charge capacity of the secondary battery.

[0025] Therefore, by obtaining a positive electrode plate using a first active material having the above ratio (Li / M) of 1.05 or more and a second active material having the above ratio (Li / M) of 1.04 or less, it becomes easier to obtain a secondary battery that combines excellent thermal stability with high charging capacity.

[0026] When a lithium transition metal composite oxide having a Ni content of 80 mol % or more relative to the total amount of the above-mentioned transition metals is used as the first active material and the second active material, the capacity of the secondary battery can be increased, but the resistance of the positive electrode plate is reduced, so that the potential of the secondary battery is likely to increase and the thermal stability is likely to decrease. Therefore, from the viewpoint of achieving both excellent thermal stability and high charging capacity, it is preferable to use a lithium transition metal composite oxide having a ratio (Li / M) in the above range, particularly when using a first active material and a second active material having a large Ni content in the transition metals.

[0027] The crystallite size of the second active material may be 800 nm or more, 850 nm or more, or 900 nm or more. The crystallite size of the second active material may be 800 nm or more and 2000 nm or less, 800 nm or more and 1500 nm or less, 850 nm or more and 1200 nm or less, or 900 nm or more and 1100 nm or less. The crystallite size of the second active material is the size of the crystallite contained in the single particle when the second active material is a single particle, and is the size of the crystallite contained in the primary particle constituting the secondary particle when the second active material is a secondary particle. The crystallite size can be measured by X-ray diffraction. When the crystallite size of the second active material is within the above range, the storage durability of the secondary battery can be improved. In the positive electrode plate, even when the second active material having the above crystallite size is used, the lithium transition metal composite oxide having the ratio (Li / M) in the above range is used as the first particle and the second particle. Therefore, by using the positive electrode plate, a secondary battery that achieves both excellent thermal stability and high charging capacity can be obtained.

[0028] The average particle diameter (D50) of the first active material (hereinafter also referred to as "D50") is not particularly limited as long as it is larger than the D50 of the second active material. The D50 of the first active material is preferably 12 μm or more and 20 μm or less, and may be 14 μm or more and 19 μm or less, or may be 15 μm or more and 18 μm or less. When the D50 of the first active material is within the above range, a secondary battery that achieves both excellent thermal stability and high charging capacity is easily obtained. When the first active material is a secondary particle, the D50 of the first active material is based on the particle diameter of the secondary particle. In this specification, the average particle diameter (D50) is a particle diameter at which the cumulative frequency from the smallest particle diameter in the volume-based particle size distribution is 50%. The volume-based particle size distribution can be measured by a laser diffraction type particle size distribution measuring device.

[0029] The D50 of the second active material is not particularly limited as long as it is smaller than the D50 of the first active material. The D50 of the second active material is preferably 2 μm or more and 8 μm or less, and may be 2 μm or more and 6 μm or less, or may be 4 μm or more and 6 μm or less. When the D50 of the second active material is within the above range, it becomes easier to obtain a secondary battery that has both excellent thermal stability and high charging capacity. The D50 of the second active material is based on the particle diameter of the single particle when the second active material is a single particle, and is based on the particle diameter of the secondary particle when the second active material is a secondary particle.

[0030] The first active material is preferably a secondary particle (aggregated particle) formed by aggregating primary particles, and the number of primary particles contained in the secondary particle is, for example, not less than 100. When both the first active material and the second active material are secondary particles, the number of primary particles contained in one first active material is preferably greater than the number of primary particles contained in one second active material.

[0031] The second active material is preferably at least one of a single particle and a secondary particle formed by agglomeration of three or less primary particles, and may be at least one of a single particle and a secondary particle formed by agglomeration of two primary particles. The second active material may include a single particle and a secondary particle formed by agglomeration of three or less primary particles. This makes it easier to obtain a secondary battery that has both excellent thermal stability and high charging capacity. The particle size of the single particle or primary particle constituting the second active material may be 0.7 μm or more, 0.8 μm or more, or 1 μm or more, for example, 0.7 μm to 8 μm, or 0.8 μm to 6 μm.

[0032] The mass ratio (first active material / second active material) of the first active material and the second active material contained in the positive electrode plate is preferably 5 / 5 to 8 / 2, and may be 5 / 5 to 7 / 3, or may be 6 / 4 to 7 / 3. By having the mass ratio (first active material / second active material) within the above range, the filling property of the first active material and the second active material in the positive electrode plate can be improved, and the output and capacity of the secondary battery can be improved.

[0033] The positive electrode plate may have an active material layer including a first active material and a second active material, and the active material layer may be formed on a positive electrode current collector. The positive electrode current collector is a metal foil made of an aluminum material such as aluminum or an aluminum alloy. The positive electrode plate may have a tab made of an aluminum material.

[0034] In addition to the first active material and the second active material, the active material layer may contain other positive electrode active materials, and may also contain a conductive material, a binder, etc. Of the total amount of positive electrode active materials contained in the active material layer, the content of the first active material and the second active material is preferably 95 mass% or more and 100 mass% or less, more preferably 95 mass% or more and 99 mass% or less, and may be 96 mass% or more and 98 mass% or less.

[0035] The conductive material may be, for example, a carbon material. The carbon material may be, for example, one or more selected from the group consisting of fibrous carbon, carbon black (acetylene black, ketjen black, etc.), coke, and activated carbon. The fibrous carbon may be, for example, carbon nanotubes (CNT). The CNT may be a single-walled carbon nanotube (SWCNT) or a multi-walled carbon nanotube such as a double-walled carbon tube (DWCNT).

[0036] The binder may be, for example, one or more selected from the group consisting of styrene butadiene rubber (SBR), polyvinylidene fluoride (PVdF), and polytetrafluoroethylene (PTFE).

[0037] The positive electrode plate can be manufactured, for example, by forming an active material layer containing a first active material and a second active material on a positive electrode current collector. The active material layer can be formed by applying a slurry containing the first active material and the second active material onto the positive electrode current collector, drying it, and compressing it. The slurry can further contain a conductive material, a binder, and a solvent such as N-methyl-2-pyrrolidone (NMP).

[0038] (Nonaqueous electrolyte secondary battery) The secondary battery may include an electrode assembly having the above-mentioned positive electrode plate, negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate, and an electrolyte. The secondary battery may further include a battery case that contains the electrode assembly and the electrolyte.

[0039] The electrode body may be a laminated electrode body composed of a laminate in which a positive electrode plate, a negative electrode plate, and a separator are laminated, or may be a wound electrode body in which the laminate is wound. The laminated electrode body may have a quadrangular shape in a plan view, preferably a square or rectangular shape, and more preferably a rectangular shape. The wound electrode body may be a flat wound electrode body pressed after winding the laminate.

[0040] The negative electrode plate may have a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector. The negative electrode current collector is, for example, a metal foil made of a copper material such as copper or a copper alloy. The negative electrode active material layer includes a negative electrode active material and may further include one or both of a conductive material and a binder.

[0041] Examples of the negative electrode active material include carbon-based active materials containing carbon (C) atoms such as graphite; and metal-based active materials containing metal elements such as metal simple substances or metal oxides containing elements selected from the group consisting of silicon (Si), tin (Sn), antimony (Sb), bismuth (Bi), titanium (Ti), and germanium (Ge). Examples of the conductive material include carbon materials such as fibrous carbon, carbon black (e.g., acetylene black, ketjen black), coke, and activated carbon. Examples of the fibrous carbon include those described above. Examples of the binder include cellulose-based binders such as carboxymethyl cellulose (CMC), and styrene butadiene rubber (SBR).

[0042] The separator may be a porous sheet (film, nonwoven fabric, etc.) made of a resin such as polyethylene, polypropylene, polyester, cellulose, or polyamide. The porous sheet may have a single-layer structure or a multi-layer structure of two or more layers. The separator may have a functional layer on the surface of the porous sheet. The functional layer may be at least one of a heat-resistant layer and an adhesive layer for bonding to a positive electrode plate and a negative electrode plate.

[0043] The electrolyte may be a non-aqueous electrolyte, for example, a non-aqueous solvent such as an organic solvent containing a supporting salt. Examples of the non-aqueous solvent include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC). The electrolyte may contain one or more of these non-aqueous solvents. Examples of the supporting salt include lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), and lithium fluoroborate (LiBF4). The electrolyte may contain one or more of these supporting salts. The electrolyte may further contain additives such as vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and fluoroethylene carbonate.

[0044] The battery case is preferably made of metal, and can be formed using, for example, aluminum, an aluminum alloy, iron, an iron alloy, or the like. EXAMPLES

[0045] The present disclosure will be described more specifically below with reference to examples and comparative examples.

[0046] [Analysis of the Compositions of the First Active Material and the Second Active Material] The compositions of the first and second active materials were analyzed by high-frequency inductively coupled plasma (ICP) optical emission spectrometry.

[0047] [Measurement of average particle size (D50) of first active material and second active material] The average particle diameters (D50) of the first active material and the second active material were measured using a laser diffraction particle size distribution measuring device ("Mastersizer-3000", manufactured by Malvern Panalytical).

[0048] [Crystallite size measurement] The crystallite size of the second active material was calculated from the peak intensity of the (104) plane using an X-ray diffractometer ("SmartLab", manufactured by Rigaku).

[0049] [Production Example 1] (Preparation of First Active Material) Ni 0.80 Co 0.05 Mn 0.15 A transition metal compound represented by (OH)2 was mixed with LiOH and then fired to obtain a first active material which was a lithium transition metal composite oxide, had a ratio (Li / M) of the number of moles of Li to the total number of moles of transition metals (M) of 1.05, and had an average particle diameter (D50) of 17.2 μm.

[0050] The NiCoMn composite hydroxide and the lithium compound were mixed and fired at 700 to 1000° C. to obtain first active materials which were lithium transition metal composite oxides and had ratios (Li / M) of the number of moles of Li to the total number of moles of transition metals (M) of 1.03, 1.07, 1.09, and 1.12. The average particle diameters of these first active materials were within the range of 12 μm to 20 μm.

[0051] (Preparation of positive electrode plate (r1)) A positive electrode plate (r1) was produced by the following procedure using each of the first active materials having the ratio (Li / M) obtained above. First, 97.5 parts by mass of the first active material, 1.5 parts by mass of carbon black as a conductive material, and 1.0 parts by mass of polyvinylidene fluoride (PVdF) as a binder were mixed, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added to obtain a slurry. The slurry was applied to an aluminum foil as a positive electrode current collector, dried, and rolled to a predetermined thickness using a rolling roller. As a result, a density of 3.30 g / cm was obtained on the aluminum foil. 3The positive electrode plate (r1) was cut to a predetermined size and an aluminum tab was attached to obtain the positive electrode plate (r1).

[0052] (Preparation of electrolyte) An electrolyte solution was prepared by adding lithium hexafluorophosphate (LiPF6) as a supporting salt to a mixed solvent prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) as a non-aqueous solvent in a ratio of EC:EMC = 30:70 (volume ratio) to give a concentration of 1 mol / L per 1 L of the mixed solvent, and adding vinylene carbonate (VC) to give a content of 0.3 mass% relative to the total mass of the mixed solvent.

[0053] (Preparation of test cell (r1)) Using the positive electrode plate (r1) obtained above, a test cell (r1) was prepared by the following procedure. The positive electrode plate (r1) and a lithium metal plate as a counter electrode of the positive electrode plate (r1) were laminated through a polyolefin separator to obtain a laminated electrode body. The laminated electrode body was housed in a battery case made of an aluminum laminate sheet, and the electrolyte prepared above was poured in, and the opening was sealed to obtain a test cell (r1).

[0054] Each test cell (r1) was subjected to a current density of 0.2 mA / cm under a temperature condition of 25°C. 2 So, 4.3V vs. Li / Li + The battery was charged at a constant current until the potential reached 4.3V vs. Li / Li. + At a potential of 0.04 mA / cm 2 The charge capacity per unit mass of the first active material was measured by constant voltage charging until the current density reached 4.1 V vs. Li / Li relative to the total capacity of the test cell (r1) during charging of the test cell (r1). + The capacity ratios at the above potentials were calculated, and the results are shown in FIG.

[0055] FIG. 1 is a plot of the results shown in Table 1, and shows the charge capacity [mAh / g] and the charge current density [mAh / g] at 4.1 V vs. Li / Li when a test cell (r1) having a positive electrode plate (r1) formed using the first active material was charged. + 1 is a graph plotting the percentage of capacity at the above potentials against the ratio (Li / M) of the number of moles of lithium (Li) to the total number of moles of transition metals (M) in the first active material. From the graph shown in FIG. 1 and Table 1, when the above ratio (Li / M) of the first active material is below 1.05, the overall capacity when the test cell (r1) is charged is 4.1V vs. Li / Li + It can be seen that the proportion of capacitance increases at potentials above this level.

[0056] [Table 1]

[0057] [Production Example 2] (Production of second active material) Ni 0.83 Co 0.12 Mn 0.05 A second active material was obtained by mixing a transition metal compound represented by (OH)2 with LiOH and calcining the mixture, which was a lithium transition metal composite oxide and had a ratio (Li / M) of the number of moles of Li to the total number of moles of transition metals (M) of 1.01. The average particle size (D50) of the second active material was 5.9 μm and the crystallite size was 965 nm.

[0058] The NiCoMn composite hydroxide and the lithium compound were mixed and fired at 700 to 1000° C. to obtain second active materials which were lithium transition metal composite oxides and had ratios (Li / M) of the number of moles of Li to the total number of moles of transition metals (M) of 0.98, 1.00, 1.04, 1.07, and 1.10. The average particle diameters of these second active materials were in the range of 2 μm to 8 μm, and the crystallite sizes were in the range of 800 nm or more.

[0059] (Preparation of positive electrode plate (r2)) A positive electrode plate (r2) was obtained in the same manner as described for producing the positive electrode plate (r1), except that the second active material was used instead of the first active material.

[0060] (Preparation of test cell (r2)) A test cell (r2) was obtained by the same procedure as described for the preparation of the test cell (r1), except that a positive electrode plate (r2) was used instead of the positive electrode plate (r1).

[0061] The test cell (r2) was subjected to constant current charging and low voltage charging in the same manner as the test cell (r1), and the charge capacity per unit mass of the second active material [mAh / g] was measured. In addition, the charge capacity of the test cell (r2) at 4.1V vs. Li / Li relative to the total capacity of the test cell (r2) during charging was + The capacity ratios at the above potentials were calculated, and the results are shown in FIG.

[0062] FIG. 2 is a plot of the results shown in Table 2, and shows the charge capacity [mAh / g] and the charge current density [mAh / g] at 4.1 V vs. Li / Li when a test cell (r2) having a positive electrode plate (r2) formed using the second active material was charged. + 2 is a graph plotting the percentage of capacity at the above potentials versus the ratio (Li / M) of the number of moles of lithium (Li) to the total number of moles of transition metals (M) in the second active material. From the graph shown in FIG. 2 and Table 2, it can be seen that when the ratio (Li / M) of the first active material exceeds 1.04, the charge capacity when the test cell (r2) is charged is significantly reduced.

[0063] [Table 2]

[0064] [Examples 1 to 3, Comparative Examples 1 to 3] (Preparation of positive electrode plate) A positive electrode active material was prepared by mixing a first active material and a second active material having a ratio (Li / M) shown in Table 3 at a ratio of first active material:second active material = 6:4 (mass ratio). A positive electrode plate was obtained by the procedure described in the preparation of the positive electrode plate (r1), except that the positive electrode active material was used instead of the first active material.

[0065] (Preparation of non-aqueous electrolyte secondary battery) A non-aqueous electrolyte secondary battery was obtained in the same manner as described for producing the test cell (r1), except that the positive electrode plate (r1) obtained above was used instead of the positive electrode plate (r1).

[0066] The non-aqueous electrolyte secondary battery was subjected to constant current charging and low voltage charging in the same manner as the test cell (r1), and the charge capacity per unit mass of the positive electrode active material [mAh / g] was measured. + The capacity ratios at the above potentials were calculated, and the results are shown in Table 3.

[0067] [Table 3]

[0068] As shown in Table 2, it can be seen that a positive electrode plate using a positive electrode active material including a first active material having a ratio (Li / M) of 1.05 or more and a second active material having a ratio (Li / M) of 1.04 or less can provide a nonaqueous electrolyte secondary battery that achieves both high charging capacity and excellent thermal stability.

[0069] [Evaluation of filling] The first active material having the above ratio (Li / M) of 1.05 and the second active material having the above ratio (Li / M) of 1.01 were mixed in the mass ratio shown in Table 4, and the density was measured when pressed under a pressure of 200 Pa. The results are shown in Table 4.

[0070] [Table 4]

[0071] As shown in Table 4, when the first particle / second particle (mass ratio) is in the range of 5 / 5 to 8 / 2, the density is 3.40 g / cm 3 It is understood that good filling properties can be obtained.

Claims

1. A first active material is a lithium transition metal composite oxide, and a second active material has an average particle diameter (D50) smaller than that of the first active material and is also a lithium transition metal composite oxide, The crystallite size of the second active material is 800 nm or more; the ratio (Li / M) of the number of moles of lithium (Li) to the total number of moles of transition metals (M) in the first active material is 1.05 or more; A positive electrode plate, wherein a ratio (Li / M) of the number of moles of lithium (Li) to the total number of moles of transition metals (M) in the second active material is 1.04 or less.

2. 2. The positive electrode plate according to claim 1, wherein a ratio (Li / M) of the number of moles of lithium (Li) to the total number of moles of transition metals (M) in the first active material is 1.12 or less.

3. 2. The positive electrode plate according to claim 1, wherein a ratio (Li / M) of the number of moles of lithium (Li) to the total number of moles of transition metals (M) in the second active material is 0.98 or more.

4. 2. The positive electrode plate according to claim 1, wherein a ratio (Li / M) of the number of moles of lithium (Li) to the total number of moles of transition metals (M) in the second active material is 1.01 or more.

5. The positive electrode plate according to claim 1 , wherein a mass ratio of the first active material to the second active material (first active material / second active material) is 5 / 5 or more and 8 / 2 or less.

6. The positive electrode plate according to claim 1 , wherein the first active material has an average particle diameter (D50) of 12 μm or more and 20 μm or less.

7. The positive electrode plate according to claim 1 , wherein the second active material has an average particle diameter (D50) of 2 μm or more and 8 μm or less.

8. The positive electrode plate according to claim 1 , wherein each of the first active material and the second active material contains 80 mol % or more of nickel (Ni) with respect to a total amount of transition metals.

9. The positive electrode plate according to claim 1 , wherein the second active material is at least one of a single particle and a secondary particle formed by aggregation of three or less primary particles.

10. An electrode assembly having a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate according to any one of claims 1 to 9; and an electrolyte.

Citation Information

Patent Citations

  • Non-aqueous electrolyte lithium secondary battery

    JP1995114942A

  • Battery anode manufacturing method and lithium ion secondary battery

    JP2012054136A

  • Lithium secondary battery

    JP2013016377A

  • Mix active material for lithium secondary battery, electrode for lithium secondary battery, and lithium secondary battery

    JP2015026594A

  • Non-aqueous electrolyte secondary battery

    JP2021163542A

Cited By

  • Lithium-ion secondary battery

    WO2026181912A1

  • Nonaqueous electrolyte secondary battery

    WO2026181913A1